Antimicrobial activities of some arid medicinalplants of Rajasthan (Indian Journal of Arid Horticulture, 2013)
Arid region of Rajasthan is a potential source of et al.,1999, Akhtar et al.,1997, Khan et al.,1996, Kapoor  medicinal plants, covers most of the north-western part of and Kumar,2005, Kapoor et al.,2007, Kapoor and Rajasthan state. Most of the medicinal plants of Rajasthan Mishra,2013, Kapoor et al.,2011, Kapoor et al.,2012,  Desert belong to the families such as Apiaceae, Kapoor and Lakhera, 2013, Kapoor and Pandita, 2013.  Asclepiadaceae, Asteraceae, Cactaceae, Casalpiniaceae, From the arid region of Rajasthan five medicinal  Capparidaceae, Chenopodiaceae, Convolvulaceae, plants like Crotalaria burhia, Euphorbia caducifolia,  Cucurbitaceae, Cyperaceae, Euphorbiaceae, Fabaceae, Leptadenia pyrotechnica, Clitoria ternatea and Tephrosia  Mimosaceae, Molluginaceae, Solanaceae and purpurea were screened for their antimicrobial activities. Zygophyllaceae etc.
Keywords: micro-organisms; sulphides; isothiocynates